Dilemmas of public participation in science policy. (4th March 2018) - Rowe, Gene; Watermeyer, Richard Patrick
ABSTRACT: Public participation is ubiquitous in many contemporary democratic societies – used for many purposes, and in many contexts, with particular and growing relevance for policy-making on science and technology issues. However, there is a dearth of evidence as to its qualities and benefits. We contend that the implementation and interpretation of participation faces a number of dilemmas that – together –undermine its successful adoption. In this paper, we identify and discuss six specific dilemmas that – together – may militate against the practice and development of good quality participation in science and technology policy, notably dilemmas of Timing; of Relevance; of Representation; of Evaluation; of Criticism; and of Impact. We theoretically account for these dilemmas and discuss their likely impacts. Finally, we provide some suggestions as to how the participation community might attempt to pre-empt difficulties due to these dilemmas and demonstrate participation effectiveness.